Interactions of LRRK2 in a Drosophila melanogaster model of Parkinson's disease - Kabbach, Ghassan (University of Ottawa (Canada), 2010)
Parkinson's disease is the most common movement disorder. A complex neurodegenerative disease, its cause and progressive nature are of unknown roots, making a final cure currently unattainable. Recently, mutations in LRRK2 have been deemed the most common cause of both familial and sporadic forms of Parkinson's disease. Itself a mysterious protein, it harbors pathogenic mutations in all of its complex functional domains. Here, we present a Drosophila melanogaster model of LRRK2 by creating four different human LRRK2 transgenic flies. Wild type LRRK2, and LRRK2 mutants I1122V, Y1699C, and I2020T have each demonstrated Dopamine neuron loss, complex behavioral and life span alterations, and a complex eye phenotype. Lastly, we have used the eye phenotype to conduct both a biased screen against recessive Parkinson's disease genes, and an unbiased screen against the Drosophila genome.
Keywords: Biology, Neuroscience.